Prevalence and factors associated with intimate partner violence against adult women in Brazil: National Survey of Health, 2019 - Nádia Machado de Vasconcelos; Fabiana Martins Dias de Andrade; Crizian Saar Gomes; Isabella Vitral Pinto; Deborah Carvalho Malta
ABSTRACT Objective: To estimate the prevalence and factors associated with intimate partner violence against adult women in Brazil. Methods: Quantitative cross-sectional epidemiological study using the database of the National Survey of Health 2019. The prevalence in the last 12 months and crude and adjusted prevalence ratios of intimate partner violence were calculated, stratified by sociodemographic characteristics. Results: Intimate partner violence was reported by 7.60% of Brazilian women aged from 18 to 59 years, with higher prevalence among younger women (8.96%), black women (9.05%), those with lower education level (8.55%) and low income (8.68%). After adjusted analysis, the age groups of 18-24 years old (PRadj: 1.41) and 25-39 years old (PRadj: 1.42) and income lower than one minimum wage (PRadj: 1.55) remained associated with intimate partner violence. Conclusions: Intimate partner violence was associated with younger and poorest women. This result points to the need to develop intersectoral policies, especially those aimed at reducing social inequalities and at the coping with intimate partner violence among adult women.